Rainbow bear - Martin, Bill, 1916-2004; Sampson, Michael R. (Brown Books Kids, 2024)
Young readers can learn the names of every color of the rainbow while following Little Bear as he wakes up from his hibernation and fills his hungry belly with berries!--Publisher.